PENGARUH HARGA, BRAND IMAGE DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN PRODUK OBAT BERMEREK PADA PT. BERNOFARM - Sumiati Sumiati; Deni Gea (JURNAL MANAJEMEN UNIVERSITAS BUNG HATTA, 2021)
This study aims to examine how the Price, Brand Image and quality influence on purchasing decisions for branded drug products. This research was conducted at PT. Bernofarm Tbk Padang. The data used in this study came from the answer scores obtained for distributed questionnaires. The testing methods used in this study are normality test, multicollinearity test, heterokesidity test, multiple regression analysis, then use the statistical F test, the t statistic test and the coefficient of determination test (R2) with a significance level of 5%. The results of this study indicate that the price has a significant effect on purchasing decisions for branded drug products, Brand Image has a positive but not significant effect on purchasing decisions for branded drug products while the quality of the products has a positive but not significant effect on purchasing decisions for branded drug products.